Productive and reproductive performances of young Ettawah-cross does - I. Ketut Sutama; I.G.M Budiarsana; H. Setiyanto; A. Priyanti (Jurnal Ilmu Ternak dan Veteriner, 1995)
Productive and reproductive performances of 85 heads of Ettawah-cross (Peranakan Ettawah or PE) does at first breeding were studied at the Research Institute for Animal Production, Bogor . They were fed freshly-chopped King grass (Pennisetum put7xtreophoides) and corn-husk (2 :1) ad libitum and concentrate feed was given at a rate of 300 - 400 g/head/day . During the last month of the pregnancy and lactation period the amount of concentrate feed was increased to 500 - 700 g/head/day . Sixty-five does were in pre-pubertal stage and 86 .2% reached puberty at liveweights between 16 - 21 .8 kg (mean 18 .8 t 0 .4 kg) which is about 60% of mature liveweight . Oestrus without ovulation was found in 6% of the animals which has contributed on the relatively low conception rate (64 .7%) . A high pre-weaning mortality of kids born (37 .5 %) caused production inefficiency that suggests the challenge to improve management practices . Milk yield of PE does varied widely (0 .3 - 0 .8 kg/day), hence, there is a chance for improvement towards increasing milk production in Indonesia through well planned selection program.